Research on the Effectiveness and Response Mechanism of Enterprise Anti-Shorting Strategy: Take Muddy Waters’ short sale of Anta Sports, for example - Hu, Qiying (International Journal of Global Economics and Management, 2024)
With the deepening participation of Chinese enterprises in the global capital market, Chinese concept stocks have become an important channel for overseas financing. However, since 2010, Chinese companies have been repeatedly shorted due to the trust crisis, and information disclosure problem has become the focus of attacks by short sellers. This article takes Muddy Waters short Anta Sports as an example, analyzes the strategies of Chinese stocks to deal with the short crisis, and puts forward suggestions on improving information disclosure, improving the awareness of crisis prevention and coping ability. The study found that Anta Sports successfully counter Muddy Waters’ short selling with emergency suspensions, clarification announcements and earnings reports, which not only confirmed the authenticity and integrity of its financial information, but also boosted investor confidence and gained broad support. Still, Anta still has room for improvement in the integrity and transparency of information disclosure, which is closely related to its corporate governance structure. Based on the "crisis management theory", this paper provides a comprehensive anti-short strategy for Chinese enterprises, including improving the corporate governance structure, improving the quality of information disclosure, and quickly responding to their suggestions on information disclosure content. These strategies can help enterprises to prevent and deal with the short crisis more effectively and achieve the crisis transformation.